Rekomendasi Pemilihan Tas Kulit Menggunakan Metode SAW (Studi Kasus: Mika Leather) - Yasser Yazid Mohammad; Agus Sidiq Purnomo (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2022)
In this study, the author aims to design a decision support system using the Simple Additive Weighting (SAW) method to find recommendations for leather bags. In this study there are four criteria used by the author, namely price, authenticity or level of authenticity of leather, bag dimensions in inches, gender or gender. The existence of a Decision Support System (SPK) is expected to help make it easier for prospective consumers to choose bags according to their wishes. 57 Based on the data used, as many as 54 data or worth 92.98% are appropriate, and the remaining three data or worth 7.02% are not appropriate.